Altitude estimation for a celestial navigation system based on infrared Earth measurement. (June 2019) - Gou, Bin; Cheng, Yong-mei; de Ruiter, Anton H.J.
Abstract: The navigation stars captured by the star sensor are far away from the spacecraft; this creates a strong similarity among star images at similar locations, attitudes but different altitudes, and renders the celestial navigation system (CNS) unable to measure the spacecraft altitude. This paper proposes a spacecraft altitude estimation method for the CNS based on infrared Earth measurement. An infrared Earth sensor first determines the Earth observation vector between the spacecraft and the Earth center relative to the inertial frame. The geographic distance between the Earth center and the Earth edge in the infrared Earth image is then calculated. Finally, the spacecraft altitude is estimated based on the triangle relationship between the spacecraft location, the Earth center, and the infrared Earth image's Earth edge relative to the inertial frame. Simulation results illustrate that the proposed method is extremely effective in high-accuracy altitude estimation. Compared to high-altitude missions with different altitudes, the altitude estimation accuracy is limited into 0.4% of the true altitude.